A fistful of dollars [videorecording (Blu-Ray)] - Eastwood, Clint, 1930-; Koch, Marianne, 1931-; Volonté, Gian Maria, 1933-1994 (KL studio classics., 2018)
A lean, cold-eyed, cobra-quick gunfighter arrives in a grim and dusty border town where two rival bands of smugglers terrorize the impoverished citizens. Though he receives lucrative offers of employment from each gang, his loyalty cannot be bought. He accepts both jobs and sets in motion a deadly plan to destroy the criminals, pitting one against the other in a series of brilliantly orchestrated setups, showdowns and deadly confrontations.